Differences in physico-chemical composition of loin of three sires from Duroc x Iberian cross selected according to their conformation - Utrillas M.; Soriano A.; Villafuerte S.E.; García Ruiz A. (7th International Symposium on the Mediterranean Pig, 2012)
In the study we are going to determine the influence of animal selection taking into account its anatomical conformation in relation to the physico-chemical composition and the colour of the loin from the offspring of three Duroc (DU) boars with different anatomical conformation, and Iberian sows. Thus, 29 loins from the barrows of the offspring of DU x Iberian were analyzed. All animals were reared on the same farm in intensive regimen and fed with the same type of feed. The loin and ham pH were determined 45 minutes and 24 hours postmortem. We also determined the pressure-induced weight loss, water activity, the colour (L, a* y b*) and the chemical composition (moisture, fat, protein and ashes) of the Longissimus dorsi muscle. Significant differences were found in the three pig sires studied for the content of protein and fat. In this way, the samples from the least conformed sire had the highest fat content, whereas the samples from the most conformed sire had the most protein content.
7. International Symposium on the Mediterranean Pig, 2010/10/14-16, Córdoba (Spain)